Observations of the Proton Aurora on Mars With SPICAM on Board Mars Express. Issue 2 (17th January 2018) - Ritter, B.; Gérard, J.‐C.; Hubert, B.; Rodriguez, L.; Montmessin, F.
Abstract: We report observations of the proton aurora at Mars, obtained with the Spectroscopy for the Investigation of the Characteristics of the Atmosphere of Mars (SPICAM) ultraviolet spectrograph on board Mars Express between 2004 and 2011. This is a third type of UV aurora that is discovered on Mars, in addition to the discrete and diffuse nightside aurora. It is observed only on the dayside as it is produced by the direct interaction of solar wind protons with the upper atmosphere. The auroral signature is an enhancement of the Lyman‐α emission in the order of a few kilorayleighs. The proton aurora features peak emissions around 120 to 150 km. From the full SPICAM database, limb observations have been investigated and six clear cases have been found. We identify either coronal mass ejections and/or corotating interaction regions as triggers for each of these events. Key Points: Lyman‐α signatures of proton aurora have been observed with SPICAM on board Mars Express Six limb profiles show unambiguous intensity enhancements between 120 and 150 km All detections are related to the arrival of a coronal mass ejection or a corotating interaction region at Mars